Struggling for Coherence: Analyzing Essay Writing Difficulties Among Filipino Junior High School Students - Hazel C. Ada; Aaron A. Funa (Journal of Research in Education and Pedagogy, 2025)
Despite ongoing efforts to strengthen writing instruction in the Philippines, coherence, the logical organization and flow of ideas, remains a persistent yet underexamined difficulty, particularly in essays written in Filipino. Most existing studies emphasize surface-level issues such as grammar and vocabulary, often overlooking the deeper organizational challenges students face. This study addresses that gap by exploring coherence-related difficulties among 131 Grade 7 and 8 students in a public school in Eastern Visayas, using a quantitative-descriptive design. The researchers applied the Complex Dynamic Systems Theory to understand coherence as an emergent, nonlinear skill shaped by learner characteristics and instructional context. Results revealed a mean coherence score of M = 2.26 (SD = 0.45), indicating poor to fair performance, with “ideas are very difficult to follow” scoring the lowest (M = 1.73). Contrary to common developmental assumptions, older students exhibited more coherence challenges (r = .34), and male students significantly underperformed compared with females (r = –.85). Strong positive correlations were observed between coherence and both general academic average (r = .87) and Filipino subject grade (r = .65). These findings suggest that coherence is not only linguistically demanding but also developmentally fragile, requiring targeted, differentiated instruction. The study offers new insights into how coherence may be better supported in multilingual classrooms and calls for curricular reforms that treat coherence as a core writing outcome in Filipino, not a peripheral skill.